Pengaruh Motivasi Konsumen terhadap Keputusan Pembelian Konsumen di Warung Kopi Pancong Sarijadi, Indonesia - Ramadhani, Raysha (Asosiasi Ahli Administrasi Indonesia, 2023)
The traditional coffee shop is still a favorite for the local community. Warkop which is known to be very simple is actually able to attract the attention of many people. This causes Warkop to always receive food or drink orders from consumers which are selling well. This is in line with the Warkop located in the Sarijadi area, namely the Warkop Pancong Sarijadi which has become the choice for many Polban students. Based on this, the researchers conducted research on what motivations influence the purchasing decisions of consumers (Polban students) at Warkop Pancong as their main choice for making purchases. This study uses a descriptive research method with a quantitative approach. Data collection was done through a questionnaire using Google Forms and a total sample is 101 respondents from active and passive Polban students. Data from the results of the distribution of this questionnaire were analyzed using frequency analysis, factor analysis, data normality analysis, and simple regression analysis using SPSS v.24 software. From this study, it was found that the result is consumer motivation had an effect on purchasing decisions.